Enhanced anaerobic synthesis of rhamnolipids and emulsification of crude oil by genetically engineered Pseudomonas aeruginosa strains - Feng Zhao; Yuting Wu; Lu Liu (Microbial Cell Factories)
Abstract Background Pseudomonas aeruginosa is a facultative anaerobic bacterium widely distributed in oil reservoirs. Efficient production of rhamnolipids by P. aeruginosa in anoxic environments of oil reservoirs contributes to oil displacement. How to enhance the synthesis of rhamnolipids by P. aeruginosa under anaerobic conditions has become a new scientific question. Results Pseudomonas aeruginosa SG anaerobically synthesized much lower yield of rhamnolipids than that under aerobic conditions. The key genes rmlBDAC (m), rhlABRI (h) and rhlC (c) and their combination genes were overexpressed in P. aeruginosa. Among seven genetically engineered strains, P. aeruginosa SGhm anaerobically synthesized the highest yield of rhamnolipids, 1.34 g/L, which was about 4.5-fold higher than that of the wild-type strain SG (0.24 g/L). The results of Plackett-Burman (PB) design indicated that glycerol and nitrate were the nutrient factors that significantly influenced the anaerobic production of rhamnolipids by strain SGhm. Optimization of culture medium by response surface method improved the rhamnolipids production of strain SGhm to 1.54 g/L under anaerobic conditions. Pseudomonas aeruginosa SGhm emulsified oil in anaerobic tubes through anaerobic synthesis of rhamnolipids. The percentage of oil droplets formed with a diameter of 0–5 μm was 89.4%. Conclusions Genes rmlBDAC and rhlABRI were the best overexpression combination for improvement of rhamnolipids production in P. aeruginosa under anaerobic conditions. Overexpression of key genes and optimization of medium synergistically increase rhamnolipids production of P. aeruginosa under anaerobic conditions. Pseudomonas aeruginosa SGhm is promising for emulsification of crude oil through anaerobic synthesis of rhamnolipids. This study provided an excellent microbial strain resource and nutrients for in-situ production of rhamnolipids in anoxic environments of oil reservoirs.